ROSETLineBOT: One-wheel-drive low-cost power line inspection robot design and control - (:unkn) unknown (Engineering and Scientific Research Groups, 2019)
Continuous operation of the electrical transmission lines is of great importance for today's electricity-dependent world. It is crucial to detect and diagnose a possible problem on the lines before that occurs. In general, maintenance, repair and error detection operations of the electrical transmission lines are performed by humans periodically. However, these difficult tasks contain high-risks in terms of occupational health and safety. Moreover, it is not possible to continuously inspect these lines which extend over long distances by maintenance and repair personnel. For all these reasons, it is very convenient to use robotic systems for inspection on power transmission lines. By evaluating the data which are provided from sensors and cameras of robotic systems, it would be possible to take precautions before an error occurs. Robotic systems that can move continuously along the line would be able to gather continuous and uninterrupted information. Thus, potential problems can be detected and identified in advance. In this study, a single wheel drive low-cost mobile robot is designed and controlled which can work and move on the electrical transmission lines. Because of the modular structure of the designed robot, different types of sensors can be integrated into the robot, easily. The designed low-cost robotic system will cause minimum losses in case of possible breakage. © JES 2019.
Keywords: Control control; One-wheel-drive robot; Power line inspection; ROSETLineBot